The Media and College Students: Influence on Written Responses. - Buccanero, Allyson J. (My University, 2009)
The media is an ever-present part of modern life with great potential to influence our thoughts and moods. This study investigated whether this influence existed in an undergraduate sample by random assignment to either a news segment or a portion of a National Geographic program that were judged as significantly different on levels of positive and negative tone.
Color poster with text, images, tables, and graphs.
Keywords: Press--Influence; Television programs--Influence; Mass media--Influence; News audiences--Attitudes; College students--Attitudes